The Comparative Assessment of Renal Artery Stenosis on Ultrasound and Computed Tomography Angiography in Hypertensive and Normotensive Patients - Tassadaq, Aleeza; Shah, Loqman; Farooq, Fouzia; Shaharyar, Muhammad; Mohib, Fatima; Fatima, Arooj; Zafar, Muhammad Wasim (Indus Journal of Bioscience Research, 2025)
Background: Renal artery stenosis (RAS) is a significant cause of secondary hypertension and renal dysfunction. Early and accurate detection is crucial for effective management. While computed tomography angiography (CTA) is considered highly reliable, ultrasonography (USG) remains a widely accessible and non-invasive alternative. However, the comparative diagnostic performance of these modalities in hypertensive versus normotensive patients remains an area of interest. Objectives: This study aims to compare the diagnostic accuracy of ultrasonography and CTA in detecting RAS, with a focus on differences between hypertensive and normotensive patients. Additionally, it evaluates the sensitivity, specificity, and predictive values of USG against CTA as the gold standard. Methodology: A cross-sectional study was conducted on 50 patients (divided into hypertensive and normotensive groups) suspected of having RAS. All participants underwent both Doppler ultrasonography and CTA. The degree of stenosis, peak systolic velocity (PSV), and renal-aortic ratio (RAR) were assessed via USG, while CTA provided detailed anatomical evaluation. Statistical analysis, including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and receiver operating characteristic (ROC) curve analysis, was performed. Results: Among 50 patients, 85.7% had significant RAS ≥70% stenosis on CTA. Ultrasonography demonstrated a sensitivity of 57.1% and specificity of 72.7% compared to CTA. Hypertensive patients showed higher PSV and RAR values, correlating strongly with severe stenosis p < 0.001. USG had higher diagnostic accuracy in hypertensive patients (60%) than normotensive ones 40%, though CTA remained superior in detecting mild stenosis. Conclusion: Doppler ultrasonography is a reliable, non-invasive tool for detecting hemodynamically significant RAS, particularly in hypertensive patients, but CTA offers superior precision, especially in early-stage stenosis. Combining both modalities may optimize diagnostic efficacy, with USG serving as an effective initial screening tool.